TCO-material-based anti-reflection layer, solar heat absorption coating and preparation methods of TCO-material-based anti-reflection layer and solar heat absorption coating - MA DING; RUI NA; SUI LINGJIE (2015)
The invention discloses a TCO-material-based anti-reflection layer. The TCO-material-based anti-reflection layer comprises a TCO transparent conductive oxide coating as a secondary anti-reflection layer and an SiO2(SiOx) oxide coating as a primary anti-reflection layer, wherein the SiO2(SiOx) oxide coating covers the TCO transparent conductive oxide coating. The selective solar heat absorption coating comprises a high reflection base layer with low infrared emissivity, a main absorbent coating and a TCO material-based anti-reflection layer; the main absorbent coating covers the high reflection base layer; and the TCO-material-based anti-reflection layer is stacked on the main absorbent coating. The invention further provides preparation methods of the anti-reflection layer and the solar heat absorption coating. A TCO coating is utilized as the anti-reflection layer in a sub-layer structure of a selective solar heat absorption coating, so that the anti-reflection layer has relatively good performance, and the production capacity aiming at preparation of the large-area selective solar heat absorption coating is extremely high.